USING OF PROFILE MATCHING AND BORDA METHOD IN PREDICTING THREATS COUNTRY IN ASEAN - Pius Herdasa Krisna Murti; Budisantoso Wirjodirdjo; Avando Bastari; Ahmadi Ahmadi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Every single country of this world wants to enlarge and optimize their territory. It causes every single country get competition to strengthen their country. In the other side they want some comfort condition, the condition is free from anxiety and the ability to predict threats, is a situation esired by all citizens. Not yet optimal in countermeasures and predicting the direction of the threat. The need for innovation in the method of determination according to the current state. Research based on the Decision Support System (DSS) trying will provide a solution in determining the predictor of the threat state. Using the Profile Matching method researchers try to map the profiles of countries located in the region. Providing problem solving by modifying the Profile Matching method is to start with delphi method in obtaining the determining criteria of research and weighting it with Borda technique. The criteria and weighting as the constituent criteria of the threat predictor country's strength profile, followed by the role so that the names of the threat predictor countries in Southeast Asia are obtained. The determination of the predictor state will facilitate in countermeasures or deal with it as well as provide actual information of where the threat comes from and the disertor criteria where the country can be weakened by Indonesia. Keywords: Strategic Position, threat, Southeast Asia Country, Profile Matching, Borda Method.